Clinical Usefulness of a Novel Freehand 3D Imaging Device for Radio-Guided Intraoperative Sentinel Lymph Node Detection in Malignant Melanoma. (September 2015) - Sulzbacher, Lena; Klinger, Markus; Scheurecker, Christine; Wacha, Michael; Shamiyeh, Andreas; Malek, Michael; Colletti, Patrick M.; Rubello, Domenico; Gabriel, Michael
<x xml:space="preserve">Abstract</x> Introduction Patients with invasive malignant melanoma are commonly referred for sentinel lymph node (SLN) detection. A recently proposed 3D tomographic imaging modality is freehand SPECT (declipseSPECT). This "bedside system" was originally developed to enable minimal-invasive image-guided surgery. The aim of this retrospective analysis was to assess the clinical use of this freehand detector device for image-guided lymphatic mapping in melanoma patients. Materials and Methods Thirty-nine patients (12 female and 27 male subjects) were included (age, 30–79 years). All of them had at least one location of melanoma with tumoral stage pT1b or greater in 37 and pTx in 2 patients in different sites of the body (abdomen in 4, back in 14, head and neck in 5, lower extremity in 6, and upper extremity in 10 patients). Lymphoscintigraphy was performed with 65 to 127 MBq 99mTc-nanocolloid. A 2-day protocol was applied with SPECT-CT acquisition (Brightview XCT, Philips) at day 1 and surgery using radio-guided freehand SPECT at day 2. SPECT-CT data were integrated into the 3D navigation system to enable fast and direct localization of the SLN by displaying the depth of the node from the skin surface and lateral margins in relation to the gamma probe. Results Comparable preoperative imaging and intraoperative localization was observed in 18 patients. In 14 cases, more lymph nodes were resected than detected by SPECT-CT including 1 patient without evidence of an SLN because this node was located close to the primary right ear tumor. In 10 of these patients, intraoperative freehand SPECT revealed additional sites of lymph nodes. In 7 cases, more findings were detected by SPECT-CT than surgically removed. The procedure was safe and easy to perform, and the time of surgical intervention using freehand SPECT was in the range of 36 to 133 minutes (mean time, 66.56 minutes). Conclusions Freehand SPECT detected more SLN compared with SPECT-CT, and the tracking system provided precise anatomical localization of the radioactive-labeled SLNs.